Private Roads - Erik T. Verhoef (Tinbergen Institute, 2007)
This paper studies the efficiency impacts of private toll roads in initially untolled networks. The analysis allows for capacity and toll choice by private operators, and endogenizes entry and therewith the degree of competition, distinguishing and allowing for both parallel and serial competition. Two institutional arrangements are considered, namely one in which entry is free and one in which it is allowed only after winning an auction in which patronage is to be maximized. Both regimes have the second-best zero-profit equilibrium as the end-state of the equilibrium sequence of investments. But the auctions regime approaches this end-state more rapidly: tolls are set equal to their second-best zero-profit levels immediately, and capacity additions for the earlier investments are bigger. When discreteness of capacity is relevant and limits the number of investments that can practically be accommodated, the auctions regime may therefore still result in a more efficient end-state, with a higher social surplus, although the theoretical end-state is the same as under free entry.
Keywords: R41; R48; D62; 330; Traffic congestion; second-best pricing; highway franchising; road networks; Verkehrsstau; Franchising; Verkehrsinfrastruktur; Straßenbenutzungsgebühr; Second Best; Theorie